Plan estratégico de marketing para incrementar las ventas en el almacén “de fiesta en fiesta” del cantón Quevedo año 2015 - Rodríguez García, Kety Elizabeth (2015)
From party to party since it started its business has been operating commercially in the city of Quevedo based on intuition and on a purely empirical development of their owners. With the need to increase sales and therefore the rotation of its products the proposal for the development of a strategic plan is presented because the lack of this there is an advertising deficit, causing ignorance on potential customers about the existence of This, merely offer their services to a minimum number of loyal customers from party to party, the lack of strategies to achieve a better market position did not allow changes to project benefits the store. As the market grows, so does the number of establishments in the same line of business, the same that provide the same or different products or services. The purpose of the research aims to provide the information needed to increase sales in terms of products and services related to this store, which will be reflected with increased profit margin to attract new customers. Substantial importance of exploration is to provide potential customers, products and services quality, cutting-edge models and finishes at the time expected by the consumer and a great price, always related to its completion.